Use of Recycling Agents in Asphalt Concrete Mixtures - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Although the use of recycled asphalt materials (RAM) in new asphalt mixtures can reduce the amount of virgin and nonrenewable materials required and increase the rutting resistance of pavements, it may also compromise cracking resistance. To mitigate this issue, asphalt mixtures containing RAM may require the use of a softer binder or recycling agent (RA).The TRB National Cooperative Highway Research Program's NCHRP Synthesis 586: Use of Recycling Agents in Asphalt Concrete Mixtures documents current state department of transportation (DOT) practices and procedures related to the use of RAs in asphalt mixtures containing RAM.
Keywords: Transportation and Infrastructure

Enabling DoD's Test Ranges and Infrastructure to Meet Threats and Operational Needs in the 21st Century: Unclassified Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Department of Defense operates several ranges across all service branches to test the effectiveness of military systems in the land, sea, air, space, and cyberspace domains. These ranges and infrastructure represent a critical part of the DoD acquisition and systems development process. The DoD's Office of Test and Evaluation (DOT&E) has asked the Board on Army Research and Development to assess how effectively these ranges fulfill DOT&E's mission to determine operational effectiveness and lethality of systems currently under development. This study will specifically evaluate whether these ranges are prepared to simulate threats, countermeasures, and operations against near-peer adversaries. This publication is the unclassified version of the classified report.
Keywords: Conflict and Security Issues

Assessing the Feasibility of the Strategic Long Range Cannon: Unclassified Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Army is working on a major science and technology development program to build the Strategic Long Range Cannon to fire a hypersonic projectile 1,000 miles. At the request of the Deputy Assistant Secretary of the Army for Research and Technology, the Committee on Assessing the Feasibility of the Strategic Long Range Cannon made recommendations for the U.S. Army in the following categories: organizational, operational, and technical demonstration development areas. This publication is the unclassified summary of the full, classified report.
Keywords: Conflict and Security Issues

Engineering Responses to Climate Change: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2022)
At the forum held during the 2021 annual meeting of the National Academy of Engineering, distinguished engineers gathered virtually to explore the roles that engineers can play in both mitigating and helping society adapt to climate change. Through a series of brief presentations and responses to questions from the moderator and the forum audience, the speakers discussed many of the issues at the forefront of climate-related engineering practice and policy today. This publication highlights the presentation and discussion of the event.
Keywords: Engineering and Technology; Environment and Environmental Studies

Reassessment of the Department of Veterans Affairs Airborne Hazards and Open Burn Pit Registry - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Beginning with the 1990–1991 Gulf War, more than 3.7 million U.S. service members have been deployed to Southwest Asia, where they have been exposed to a number of airborne hazards, including oil-well fire smoke, emissions from open burn pits, dust and sand, diesel exhaust, and poor-quality ambient air. Many service members, particularly those who served in Iraq and Afghanistan, have reported health problems they attribute to their exposure to emissions from open-air burn pits on military installations.
Keywords: Health and Medicine

Communities, Climate Change, and Health Equity—State-Level Implementation: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Because of historic and ongoing discriminatory policies and practices, certain populations - namely people of color, Indigenous people, and low-income communities - disproportionately suffer from the adverse impacts of extreme weather and other disasters that are exacerbated by climate change. To examine actions that could help improve climate-related health outcomes in disproportionately impacted communities, the Environmental Health Matters Initiative, a program spanning all major units of the National Academies of Sciences, Engineering, and Medicine, convened a two-day workshop Communities, Climate Change, and Health Equity - State-Level Implementation on May 24 and 26, 2022. The workshop brought together representatives from state and federal agencies, universities, community-based organizations, state and national advocacy organizations, foundations, and private sector organizations. This publication highlights the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

Review of the U.S. Global Change Research Program's Draft Decadal Strategic Plan, 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
More intense heat waves, extended wildfire seasons and other escalating impacts of climate change have made it more important than ever to fill knowledge gaps that improve society's understanding, assessment, and response to global change. The US Global Change Research Program (USGCRP) - a collection of 13 Federal entities charged by law to help the United States and the world fill those knowledge gaps - laid out proposed mechanisms and priorities for global change research over the next decade in its draft Decadal Strategic Plan 2022-2031. The draft plan recognizes that priority knowledge gaps have shifted over the past decade as demand has grown for more useful and more inclusive data to inform decision-making, and as the focus on resilience and sustainability has increased. As part of its work in advising the USGCRP since 2011, the National Academies reviewed USGCRP's draft plan to determine how it might be enhanced. Advances in the draft plan include an increased emphasis on social sciences, community engagement with marginalized groups, and promotion of diversity, equity, inclusion, and justice in the production of science. Strengthening the interconnections between the plan's core pillars and expanding opportunities for coordination among federal agencies tasked with responding to global climate change would improve the plan. The draft plan could more strongly convey a sense of urgency throughout the plan and would benefit from additional examples of key research outputs that could advance policy and decision making on global change challenges.
Keywords: Earth Sciences; Behavioral and Social Sciences

Methadone Treatment for Opioid Use Disorder: Improving Access Through Regulatory and Legal Change: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Methadone is a Food and Drug Administration- (FDA-) approved medication for treating opioid use disorder (OUD), a chronic brain disease that affects more than 2.7 million people in the United States aged 12 and older. Despite its effectiveness in saving lives, many barriers impede access to, initiation of, and retention in methadone treatment for OUD. To address these barriers, on March 3 and 4, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on "Methadone Treatment for Opioid Use Disorder: Examining Federal Regulations and Laws," at the request of the Office of National Drug Control Policy in the Executive Office of the President. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Mechanisms for Organizational Behavior Change to Address the Needs of People Living with Alzheimer's Disease and Related Dementias: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Patients diagnosed with Alzheimer's disease and related dementias (ADRD) rely on family members, their community, and the health care system for progressively increasing support over the course of their disease. These people receive care through a frequently siloed health care system across hospitals, nursing homes, ambulatory care settings, and long-term care settings, as well as community- and home-based care. As the number of people living with a diagnosis of ADRD continues to grow, so does the need to provide better support for these people and their caregivers. The National Institute on Aging (NIA) Division of Behavioral and Social Research suggests that organizational behavior change will be needed for health care systems to integrate all of the services and supports required to provide high-quality care for people with ADRD.NIA sponsored a workshop hosted by the National Academies of Sciences, Engineering, and Medicine to explore mechanisms to improve the quality of care for people living with ADRD and the potential of innovative payment models to incentivize health care systems to make the necessary systemic changes. The workshop convened a diverse array of experts in fields including nursing, geriatrics, health care economics, health care services research, quality measurement, social work, medical ethics, law, health care finance, and health care policy. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants: Proceedings of a Virtual Symposium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 28 and 29, 2022, the Board on Behavioral, Cognitive, and Sensory Sciences at the National Academies of Sciences, Engineering, and Medicine held a virtual symposium entitled Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants to gain a better understanding of social determinants influencing the recent increase in suicide risk and how currently available practice guidelines can inform community-level preventive interventions, particularly those targeting veteran populations. Presenters and participants explored the relevant social, cultural, and economic factors driving changes in suicide risk among veterans and ways that current best practices for suicide prevention and treatment can be applied at the community level. This publication summarizes the presentations and discussion of the symposium.
Keywords: Health and Medicine; Behavioral and Social Sciences

Public Liabilities Relating to Driveway Permits - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Transportation agencies across the country may face legal challenges from property owners when design or permit changes cause safety concerns or obstruct access to private driveways in the public right-of-way.The TRB National Cooperative Highway Research Program's NCHRP Legal Research Digest 85: Public Liabilities Relating to Driveway Permits evaluates the circumstances under which transportation agencies are held liable by property owners for the regulatory function of permitted and unpermitted driveways.
Keywords: Transportation and Infrastructure

Frameworks for Protecting Workers and the Public from Inhalation Hazards - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Individuals in the United States and Americans abroad are exposed to inhalation hazards from a variety of sources, and these hazards can have both short- and long-term adverse effects on health. For example, exposure to wildfire smoke, which contains particulate matter and toxic chemicals, can lead to respiratory problems, increased risk for heart attacks, and other adverse health outcomes. Individuals also may be exposed to airborne infectious agents through aerosol or droplet transmission, and as demonstrated by the COVID-19 pandemic, the individual and public health consequences of these exposures can be severe. Storms, floods, and hurricanes can increase exposure to moisture-driven hazards, such as mold, and to accidental releases from production facilities or transport vehicles that may result in chemical exposures. The current regulatory system is focused primarily on ensuring access to respiratory protection in occupational settings characterized by well-defined hazards and employer-employee relationships. With this narrow regulatory focus, the respiratory protection needs of the public and many workers are not being met. As climate change increases the incidence and severity of wildfires, hurricanes, floods, infectious disease outbreaks, and other phenomena that impact air quality and human health, it is imperative that the United States ensure that the respiratory protection needs of the public and all workers are met. Recognizing the urgent need to address the gaps in the nation's ability to meet the respiratory protection needs of the public and workers without workplace respiratory protection programs, this report makes recommendations for a framework of responsibilities and authorities that would provide a unified and authoritative source of information and effective oversight for the development, approval, and use of respiratory protection.
Keywords: Health and Medicine

Exploiting Advanced Manufacturing Capabilities: Topology Optimization in Design: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Topology optimization is a digital method for designing objects in order to achieve the best structural performance, sometimes in combination with other physical requirements. Topology optimization tools use mathematical algorithms, such as the finite element method and gradient computation, to generate designs based on desired characteristics and predetermined constraints. Initially a purely academic tool, topology optimization has advanced rapidly and is increasingly being applied to the design of a wide range of products and components, from furniture to spacecraft. To explore the potential and challenges of topology optimization, the National Academies of Sciences, Engineering, and Medicine hosted a two-day workshop on November 19-20, 2019, Exploiting Advanced Manufacturing Capabilities: Topology Optimization in Design. The workshop was organized around three main topics: how topology optimization can incorporate manufacturability along with functional design; challenges and opportunities in combining multiple physical processes; and approaches and opportunities for design of soft and compliant structures and other emerging applications. Speakers identified the unique strengths of topology optimization and explored a wide range of techniques and strengths of topology optimization and explored a wide range of techniques and achievements in the field to date. This publication summarizes the presentations and discussion of the workshop.
Keywords: Industry and Labor; Engineering and Technology

Anticipating Rare Events of Major Significance: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Intelligence Community Studies Board of the National Academies of Sciences, Engineering, and Medicine convened a 2-day virtual workshop on December 17 and 21, 2021, to explore insights from world-class experts and technologists familiar with the extensive range of issues associated with anticipating rare events—those characterized by a very low probability of occurring—of major significance. Over the course of the 2-day workshop, the speakers discussed analytical methods, computational advances, data sources, and risk assessment approaches for anticipating rare events, including natural disasters, pandemics, anthropogenic threats, and widespread technological change. This proceedings is a factual summary of the presentations and discussion of the workshop.
Keywords: Conflict and Security Issues

Data-Informed Societies Achieving Sustainability: Tasks for the Global Scientific, Engineering, and Medical Communities: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The 2030 Agenda for Sustainable Development, adopted in 2015 by all United Nations Member States, offers a "shared blueprint for peace and prosperity for people and the planet, now and into the future." The Agenda outlines 17 Sustainable Development Goals (SDGs), which address a range of global challenges, including poverty, inequality, climate change, and environmental degradation, among others. Advances in technology and the proliferation of data are providing new opportunities for monitoring and tracking the progress of the SDGs. Yet, with these advances come significant challenges, such as a lack infrastructure, knowledge, and capacity to support big data. To further examine how the global scientific, engineering, and medical communities can better facilitate the effective use of data to advance sustainability in the context of the SDGs, the National Academies of Sciences, Engineering, and Medicine’s Board on Research Data and Information and the Science and Technology for Sustainability Program convened a virtual public workshop on September 9-10, 2021. The workshop examined current efforts and initiatives to harness data and data-driven services to advance sustainability around the world. Workshop discussions also explored crosscutting issues, including strengthening the engagement of scientific, engineering, and medical communities on data-related issues, addressing disparities in the ability of societies to utilize data, and lessons learned from global experience with the COVID-19 pandemic. This publication summarizes the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

Relocation and Other Climate Adaptations on Florida's Gulf Coast: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Strategically moving communities and infrastructure - including homes and businesses - away from environmentally high-risk areas, such as vulnerable coastal regions, has been referred to as managed retreat. Of all the ways humans respond to climate-related hazards, managed retreat has been one of the most controversial due to the difficulty inherent in identifying when, to where, by whom, and the processes by which such movement should take place. To understand and respond to the unique challenges associated with managed retreat, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine sponsored a committee of experts to provide in-depth analysis and identify short- and long-term next steps for Gulf Coast communities that may need to relocate. The committee convened a series of three public workshops in the Gulf Coast region to gather information about on policy and practice considerations, research and data needs, and community engagement strategies. The workshops focused on elevating the voices of communities and individuals contemplating, resisting, undertaking, or facing barriers to relocation (including systemic issues such as structural racism), as well as individuals who have resettled and communities that have received such individuals. Each workshop included community testimonials and panels of local decision makers and experts discussing study-relevant processes and obstacles faced by communities. The first workshop was held in two parts in Houston and Port Arthur, Texas; the second workshop was held in St. Petersburg, Florida; and the third workshop was held in two parts in Thibodaux and Houma, Louisiana. This Proceedings of a Workshop-in Brief recounts the second workshop, held in July 2022 in St. Petersburg, Florida.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Artificial Intelligence Tools and Open Data Practices for EPA Chemical Hazard Assessments: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Environmental Protection Agency's (EPA’s) Integrated Risk Information System (IRIS) Program identifies and characterizes the human health hazards of chemicals found in the environment. Human health risk assessments cover hazard identification as well as dose-response analyses for cancer and noncancer outcomes that are obtained from IRIS assessments. Human health risk assessments are highly important as they are used to inform a broad range of risk-related decisions across the agency. These assessments involve systematic reviews of the scientific literature, which obtain, evaluate, and summarize information to answer a research question in a transparent manner. At the request of the Center for Public Health and Environmental Assessment within EPA's Office of Research and Development, the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore opportunities and challenges in using advances in artificial intelligence (AI) and data science to enhance human health risk assessments. The workshop was held virtually on May 25 and 26, 2022. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Rapid Expert Consultation on Critical Federal Capabilities Needed to Evaluate Real-World Safety, Effectiveness, and Equitable Distribution and Use of Medical Countermeasures During a Public Health Emergency - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has highlighted the importance of having access to real-world data and evidence to monitor and assess medical countermeasure (MCM) use and performance so policy makers can make more effective and rapid public health decisions, protect population health, and save lives. During public health emergencies, the use of MCMs, such as therapeutics, vaccines, and diagnostics, can be made available to the public under a range of regulatory access mechanisms. This Rapid Expert Consultation was produced by individual members of the Standing Committee for CDC Center for Preparedness and Response. Its aim is to review and propose modifications to an initial draft list of critical federal capabilities presented by the Centers for Disease Control and Prevention and the U.S. Food and Drug Administration that are needed to evaluate real-world safety, effectiveness, equitable distribution, access, and use of MCMs during a public health emergency. This effort draws from expert input, published literature, and lessons learned from previous public health emergencies, as well as the ongoing COVID-19 pandemic.
Keywords: Health and Medicine

Traumatic Brain Injury: A Roadmap for Accelerating Progress - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Every community is affected by traumatic brain injury (TBI). Causes as diverse as falls, sports injuries, vehicle collisions, domestic violence, and military incidents can result in injuries across a spectrum of severity and age groups. Just as the many causes of TBI and the people who experience it are diverse, so too are the physiological, cognitive, and behavioral changes that can occur following injury. The overall TBI ecosystem is not limited to healthcare and research, but includes the related systems that administer and finance healthcare, accredit care facilities, and provide regulatory approval and oversight of products and therapies. TBI also intersects with the wide range of community organizations and institutions in which people return to learning, work, and play, including the education system, work environments, professional and amateur sports associations, the criminal justice system, and others. Traumatic Brain Injury: A Roadmap for Accelerating Progress examines the current landscape of basic, translational, and clinical TBI research and identifies gaps and opportunities to accelerate research progress and improve care with a focus on the biological, psychological, sociological, and ecological impacts. This report calls not merely for improvement, but for a transformation of attitudes, understanding, investments, and care systems for TBI.
Keywords: Health and Medicine

Addressing the Adverse Consequences of Cancer Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Cancer treatment can lead to an array of significant short- and long-term physical, psychosocial, and socioeconomic consequences for patients and their families. To examine the opportunities to prevent and mitigate the adverse effects of cancer treatment, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop, Addressing the Adverse Consequences of Cancer Treatment, in November 2020. This workshop was convened by the Academies' National Cancer Policy Forum in collaboration with the Forum on Aging, Disability, and Independence. Workshop presentations and discussions described the range of adverse effects that patients with cancer may experience across the life course, and highlighted potential strategies to improve quality of life for cancer survivors and their families.
Keywords: Health and Medicine